The proceedings of Spanish Audiovisual Councils on discriminatory discourse (Communication & Society, 2021)
Mass media, and especially television, are powerful discursive instruments, responsible for the construction of social imagery through ideologically determined content. For this reason, the creation of a regulatory body with authority over the audiovisual sector in countries without one was urged by the Committee of Ministers of the Council of Europe in 2000. Spain is the only EU country without an audiovisual council with authority at the state level. Currently, only the Audiovisual Council of Catalonia (CAC), created in 2000, and the Audiovisual Council of Andalusia (CAA), which dates from 2004, operate in Spain. Within an environment increasingly marked by hate speech, this research analyzes the proceedings of the Andalusian and Catalan Audiovisual Councils between 2004 and 2019 as it pertains to discrimination against vulnerable groups. Every pronouncement made by both councils on potentially discriminatory discourses was retrieved (n=156). These were content analyzed by codifying, among others, the following variables: type of action, the source that motivated it, the disseminating media outlet, the evaluated content, the type of discrimination alleged, the decision taken, and the type of sanction imposed by the councils, as the case may be. The results indicate that most of the actions concerned involve discrimination against women, originate from third-party complaints and target content broadcast on public television.